Features of Incidence of Acute Respiratory Viral Infections and Cytomorphological Peculiarities of Nasal and Oral Mucosa in Infants Which are Influenced by Tobacco Smoke - O.V. Tyazhka; T.O. Vankhanova; L.M. Yaremenko; L.M. Yaremenko (Zaslavsky O.Yu., 2012)
The article shows features of acute respiratory disease in infants under the influence of tobacco smoke. It is found that children - passive smokers are significantly more likely to suffer from acute respiratory viral infections starting from the second year of life, they have a longer duration of the episode on the second and the incidence of complications. The paper also highlights the features of the state of nasal and oral mucosa. In infants who passively smoke, oral mucosa is more fragile, prone to trauma, which can be seen on the reduction of its moisture and increase the number of basal cells in epithelial smears. Significantly higher index of keratinization and increased number of cells with keratogialinum may probably serve as a sign of intense processes of keratinization of the compensatory adaptive nature. The signs of oral cavity dysbiosis in the form of abundant microflora of the mouth, including fungal flora, and reduced oral streptococci colonization index were revealed. Changes in the mucous membranes of the nose in children - passive smokers manifested in more mucus, violations of the proportion of goblet and ciliated cells. Such changes could significantly impede effective implementation of mucociliary clearance and reduce the protective properties of the mucous membranes. The findings suggest the need for preventive measures aimed at reducing exposure to tobacco smoke.